Schedulling Economical Thermal Power Plant 500 KV Java-Bali System Using Lagrange Multiplier. (March 2017) - Sartika, N; Abdullah, A G; Hakim, D L
Abstract: The highest cost of electricity generation operation is fuel cost. Therefore, it is necessary to optimize the thermal generator scheduling. The present study aimed at obtaining the schedule and load sharing of the electric power generation, in order to gain the minimum fuel cost, with regard to inequality and equality constraints. The data tested was the thermal generation system of 500 kV Java-Bali using daily loads. This study employed a lagrange multiplier method to perform the economic scheduling. This method is one of mathematical techniques commonly used to solve economic dispatch problems. The results of the optimation of lagrange multiplier were compared with the real condition in the field. Based on the optimation results, it was found that the lagrange multiplier method is more economical than the real condition of system.